1989
DOI: 10.1203/00006450-198910000-00015
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Adult Rat Intestinal Heme Oxygenase by Metalloporphyrins

Abstract: ABSTRACT. We determined the inhibitory effects of concentrations of tin-and zinc protoporphyrin (1-100 pM) and mesoporphyrin (0.1-10 pM) on the in vitro heme oxygenase (HO) (E.C.1.14.99.3) activity in liver, spleen, and intestine 13, 000 % g tissue supernatants from fasted adult male Wistar rats through measurement of carbon monoxide by gas chromatography. All four metalloporphyrins inhibited intestinal HO, under the light-limited conditions of these experiments. The zinc porphyrins showed a clear concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…However, the results of the present experiments lead us to believe that the CO was produced from organic mole cules, including NADPH, in the tissue prep arations under the influence of ambient light formed in the dark. This assay modification allowed us to explain the previously puzzling observation that rat intestinal HO appeared to be uninhibitable by SnPP at concentra tions which significantly inhibited spleen and liver HO [30], Comparison of results with assays performed in the dark versus those performed in the light showed that light exposure negated the SnPP-caused in hibition of intestinal HO observed in the dark [31]. These studies showed that intesti nal HO responds differently to SnPP than liver and spleen.…”
Section: Discussionmentioning
confidence: 79%
“…However, the results of the present experiments lead us to believe that the CO was produced from organic mole cules, including NADPH, in the tissue prep arations under the influence of ambient light formed in the dark. This assay modification allowed us to explain the previously puzzling observation that rat intestinal HO appeared to be uninhibitable by SnPP at concentra tions which significantly inhibited spleen and liver HO [30], Comparison of results with assays performed in the dark versus those performed in the light showed that light exposure negated the SnPP-caused in hibition of intestinal HO observed in the dark [31]. These studies showed that intesti nal HO responds differently to SnPP than liver and spleen.…”
Section: Discussionmentioning
confidence: 79%
“…ZnMP induces polyubiquitination of NS5A and display anti-viral activity, we found ZnMP an attractive choice, and we chose to use mainly ZnMP because of the profound effects on Bach117, because mesoporphyrin derivatives lack reactive vinyl groups and are therefore more chemically stable than protoporphyrin derivatives38, and because it is taken up by intact liver cells far better than other zinc derivatives such as bisglycol-deuteroporphyrin congener39. Zinc porphyrins, under some circumstances, may be toxic to hematopoietic cells in vitro40.…”
Section: Discussionmentioning
confidence: 99%
“…Because SnMP inhibits intestinal HO (Vreman et al, 1989) and decreases intestinal heme–iron absorption (Boni et al, 1993), this may account for the iron deficiency-like anemia that results after long-term SnMP exposure. Kappas et al (1993) reported that the deficiency was easily reversed by supplementation with iron.…”
Section: Pharmacodynamics Of Metalloporphyrinsmentioning
confidence: 99%